Popular piety and the records of the unestablished churches 1460–1660 - Cross, Claire (Studies in church history, 1975)
John foxe in his long account of ‘the grievous affliction of good men and women in the diocese of Lincoln’, based on Lincoln episcopal records for 1521, gave over a quarter of a page to the Colins family of Ginge, near West Hendred in Berkshire. At a time of wholesale detection of lollards, when episcopal officials had succeeded in getting neighbour to inform against neighbour, John Edmunds revealed what he knew about Richard Colins, Alice, his wife, and their daughter, Joan.This Richard Colins, as he was a great doer among these good men, so was he much complained upon by divers. . . for bringing with him a book called The King of Beeme [Bohemia] into their company, and did read thereof a great part unto them in this Edmunds’ house of Burford.This Alice likewise was a famous woman among them, and had a good memory, and could recite much of the scriptures, and other good books. And therefore when any conventicle of these men did meet at Burford, commonly she was sent for to recite unto them die declaration of the Ten Commandments, and the epistles of Peter and James.This Joan also, following her father’s and mother’s steps, was noted for that she had learned with her father and mother, the Ten Commandments, the Seven Deadly Sins, the Seven Works of Mercy, the Five Wits Bodily and Ghostly, the Eight Blessings, and five chapters of St James’s epistle.